PEMIKIRAN TEOLOGI TEOSENTRIS MENUJU ANTROPOSENTRIS HASAN HANAFI - Achmad Faisol Haq (Bahasa Indonesia, 2020)
Theology is the foundation for a religion, whereas the thought of the theology of a thinker, will have a very significant impact in the reality of life, because being a religious foundation, the theology is a foothold in the behavior of a person, therefore in today's contemporary period there needs to be a theology that can be applied in daily life, the discussion of a theology is not only theological, but also needs a theology that anthropocentric, this anthropocentric theology, carried out by Hasan Hanafi, is based on a theoccentric theology whose nature is digitized in the dilectic of the discussion, then under the anthropocene so that it can be directly implemented in the daily life of society. In this study tried to examine the theological thinking towards the anthropocentric Hasan Hanafi. This research is a library study, looking for sources of references related to the theme of research, as well as taking from the opinions of various figures, then elaborated and observed until it becomes a research paper